EXAMINING OF POST-PANDEMIC CHALLENGES FACED BY THE SMALL AND MEDIUM-SIZED ENTERPRISES (SMES) IN SYLHET REGION - Uddin, Md Riaj; Uzzol, Anamul Haque (Universitas Nusa Cendana, 2024)
This study examines the context of the small and medium business (SME) environments for enterprising conditions in Sylhet following COVID-19. This article aims to highlight the most common legal hurdles small enterprises face during business management. 52 proper samples were randomly selected from the SMEs; these are common in the area. It has been utilizing various blended approaches which include qualitative and quantitative ones. Some of these business categories include retail, pharmacy, restaurant, mobile repair shops, and fast food. The research used both the structured and unstructured, a critical appraisal based on prior research on organizational learning. This paper emphasizes the importance of SMEs in the economic progress of the Sylhet region. However, with all these possibilities, there are numerous problems that an SME is faced with. Among them are limited access to finance, sourcing requirement of inputs, high operating costs, unfavorable market conditions, and impacts from shifting politically unstable environment. Keywords: Entrepreneurial Environment; Sylhet-Based SMEs; Economic Growth; Funding Challenges